Framing the land of the Northern Lights. (September 2019) - White, Paul; Morgan, Nigel; Pritchard, Annette; Heimtun, Bente
Abstract: The development of affinities between the production and consumption of people and place is crucial for tourism development. We trouble front and backstage distinctions to examine how destinations are framed and critically explore the power of the imaginary in shaping how individuals apprehend and in turn create social worlds. Combining critical discourse analysis with stakeholder interviews, we scrutinise an influential television travel documentary as an instrument of cultural pedagogy, which recycles, recreates and re-enacts the tourism imaginary. The paper's distinctive contribution is to show the multiple means through which travel journalism enrols tourists through imagined portrayals of people and place within globalised cultural texts by highlighting the multi-dimensional workings of power in and through a framing of Northern Norway. Highlights: Scrutinises travel documentaries as instruments of cultural pedagogy Demonstrates tourism's framing of 'the North' in Arcticist discourses Discusses travel journalism as a constituent of the tourism imaginary Examines the layers of affinity between globalised scripts and the imaginary in reordering social relations Highlights the multi-dimensional workings of power in and through media framing